Kepribadian Guru - Nurhaliza, Siti; Juro, Az-Zahra (Lembaga Yasin AlSys, 2023)
To become a teacher, you must have a strong and admirable personality. The character required of a teacher is steady, stable, mature, wise and authoritative. The teacher's personality has a great influence on the student learning process. Experience shows that problems such as motivation, discipline, social behavior, academic achievement, and the desire to continue learning from students stem from the teacher's personality. This study aims to clarify the character of the teacher. This type of research is qualitative research that uses a series of sentences to describe the data. The method used in this research is descriptive method. The results of this study indicate that a good teacher who is liked by his students must have good attitudes and behavior. Because the teacher's attitude reflects the character of that person. Oemar Hamarik said that a good teacher is one that his students like in class, namely democratic, cooperative, kind, patient, fair, consistent, open, he said a good and warm-hearted teacher.